2012
DOI: 10.3390/medicina48070050
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Problems in Children with Benign Childhood Epilepsy With Centrotemporal Spikes Treated and Untreated with Antiepileptic Drugs

Abstract: The aim of this study was to investigate behavioral problems in two groups of children with benign childhood epilepsy with centrotemporal spikes (BECTS), i.e., those treated with antiepileptic drugs and those not treated in order to identify the factors associated with behavioral problems. Material and Methods. In total, 20 newly diagnosed untreated, 23 treated patients with BECTS, and 20 patients with acute/subacute peripheral nervous system disorders as a comparison group (aged 6–11 years) were examined. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 27 publications
0
16
0
1
Order By: Relevance
“…A Tanzanian‐based study found no evidence of behavior exacerbation with AEDs, including phenobarbital, but assessments were based solely on parental feedback, and access to AEDs was limited, with only 48% of the study group receiving therapy This is supported by studies from resource‐equipped settings as well. In contrast, other studies reported that patients with CECTS on AEDs were more likely to have social problems, aggressive behavior, and attention problems and be anxious/depressed . The study group alluded that this finding was related to ongoing seizures rather than specifically AEDs.…”
Section: Resultsmentioning
confidence: 56%
“…A Tanzanian‐based study found no evidence of behavior exacerbation with AEDs, including phenobarbital, but assessments were based solely on parental feedback, and access to AEDs was limited, with only 48% of the study group receiving therapy This is supported by studies from resource‐equipped settings as well. In contrast, other studies reported that patients with CECTS on AEDs were more likely to have social problems, aggressive behavior, and attention problems and be anxious/depressed . The study group alluded that this finding was related to ongoing seizures rather than specifically AEDs.…”
Section: Resultsmentioning
confidence: 56%
“…2 However, the frequently recurring seizures, neuropsychological dysfunctions and behavioral abnormalities encountered in children with BECTS are factors that favor prophylaxis with antiepileptic drugs (AEDs). [3][4][5][6] When treatment is planned, priority should be given to monotherapies with agents that have established antiepileptic effects and whose adverse effects are clearly understood. 7 Levetiracetam (LEV) has recently been considered as the initial monotherapy for typical BECTS.…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis for seizure outcome in BECTS is excellent; most patients have less than 10 seizures, and seizure activity is expected to cease by adulthood (Blom & Heijbel, 1982; Camfield & Camfield, 2002; Dalla Bernardina, Sgro, & Fejerman, 1995; Loiseau, Duche, Cordova, Dartigues, & Cohadon, 1988; Panayiotopoulos, 1999). However, a growing body of literature has documented subtle cognitive and/or behavioral problems in children with BECTS, particularly affecting language function (Baglietto et al, 2001; Danielsson & Petermann, 2009; Ebus, Overvliet, Arends, & Aldenkamp, 2011; Goldberg-Stern et al, 2010; Jurkeviciene et al, 2012; Northcott et al, 2005; Overvliet, Aldenkamp, Klinkenberg, Nicolai, et al, 2011; Overvliet, Besseling, van der Kruijs, et al, 2013; Overvliet, Besseling, et al, 2011; Samaitiene, Norkuniene, Jurkeviciene, & Grikiniene, 2012; Samaitiene, Norkuniene, Tumiene, & Grikiniene, 2013; Verrotti, Filippini, Matricardi, Agostinelli, & Gobbi, 2014; Volkl-Kernstock, Bauch-Prater, Ponocny-Seliger, & Feucht, 2009). …”
Section: Introductionmentioning
confidence: 99%